Pompeian Peristyle Gardens - Simelius, Samuli (Studies in Roman Space and Urbanism, 2022)
This book examines how Pompeian peristyle gardens were utilized to represent the socioeconomic status of Roman homeowners, introducing fresh perspectives on how these spaces were designed, used, and perceived. Pompeian Peristyle Gardens provides a novel understanding of how the domus was planned, utilized, and experienced through a critical examination of all Pompeian peristyles - not just by selecting a few well-known examples. This study critiques common scholarly assumptions of ancient domestic space, such as the top-down movement of ideas and the relationship between wealth and socio-political power, though these possibilities are not excluded. In addition, this book provides a welcome contribution to exploring the largely unexamined middle class, an integral part of ancient Roman society. Pompeian Peristyle Gardens is of interest to students and scholars in art history, classics, archaeology, social history, and other related fields.